Manganese pyrosilicates as novel positive electrode materials for Na-ion batteries. Issue 5 (28th March 2018) - Renman, Viktor; Valvo, Mario; Tai, Cheuk-Wai; Gómez, Cesar Pay; Edström, Kristina; Liivat, Anti
Abstract : Desodiation of the Na2 Mn2 Si2 O7 –carbon nanocomposite exhibits unique rearrangements in a Mn-coordination environment. Abstract : A carbon-coated pyrosilicate, Na2 Mn2 Si2 O7 /C, was synthesized and characterized for use as a new positive-electrode material for sodium ion batteries. The material consists of 20–80 nm primary particles embedded in a ≈10 nm-thick conductive carbon matrix. Reversible insertion of Na + ions is clearly demonstrated with ≈25% of its theoretical capacity (165 mA h g −1 ) being accessible at room temperature at a low cycling rate. The material yields an average potential of 3.3 V vs. Na + /Na on charge and 2.2 V on discharge. DFT calculations predict an equilibrium potential for Na2 Mn2 Si2 O7 in the range of 2.8–3.0 V vs. Na + /Na, with a possibility of a complete flip in the connectivity of neighboring Mn-polyhedra – from edge-sharing to disconnected and vice versa . This significant rearrangement in Mn coordination (≈2 Å) and large volume contraction (>10%) could explain our inability to fully desodiate the material, and illustrates well the need for a new electrode design strategy beyond the conventional "down-sizing/coating" procedure.